Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1932
DOI: 10.1002/jcp.1030010211
|View full text |Cite
|
Sign up to set email alerts
|

Nerve impulses from single receptors in the eye

Abstract: Recent studies in sensory physiology have provided a new approach to the problem of the mechanism of sense organs. The discharge of nerve impulses in the afferent fibers from various receptors has been studied in preparations in which the activity can be limited to a single end organ and its attached nerve fiber. The more complete analysis characteristic of this approach is best exemplified in the work done on tension, touch, and pressure receptors (Adrian, '26; Adrian and Zotterman, '26 ; Bronk, '29 ; Matthew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
90
0

Year Published

1932
1932
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 290 publications
(96 citation statements)
references
References 12 publications
6
90
0
Order By: Relevance
“…In accordance with established usage the reciprocal of the energy at a given wave length necessary to produce a constant response is defined as the visibility at that wave length (Hecht and Williams, 1922). Thus in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…In accordance with established usage the reciprocal of the energy at a given wave length necessary to produce a constant response is defined as the visibility at that wave length (Hecht and Williams, 1922). Thus in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The response of the single receptor cell in the eye of Limulus, in terms of impulses discharged in its attached nerve fiber, has been described in two previous publications (Hartline and Graham, 1932;Hartline, 1934). When stimulating lights of different wave lengths but of approximately equal energy content are used it is found that the response to green light is stronger than the response to either red or violet; i.e., the latent period is shorter, the initial and maximum frequency is higher and, for short flashes, the total number of impulses is larger; with prolonged exposure the final level of frequency is higher.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations